2020
DOI: 10.17306/j.jard.2020.01316
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use of farm mechanization services amongst emerging farmers in North West province of South Africa

Abstract: There are low levels of farm mechanization in South Africa despite government efforts to improve access to infrastructure and finance through the Comprehensive Agricultural Support Programme (CASP). The objective of this study is to assess the levels of mechanisation in the emerging sector and the determinants thereof. The sample size consisted of 163 randomly selected maize and sunflower emerging farmers in North West Province. Data was collected using a structured questionnaire. Descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, this study aims to assess labor shortages related to different farm activities, estimate the WTP for mechanization services, and identify policy options for promoting smallholder mechanization services in Malawi. Previous studies in SSA and Asia showed that smallholder farmers are willing to pay for tractor‐hire services for agricultural activities such as land preparation, weeding, harvesting, threshing, and transport (Hodjo et al, 2021; Houssou et al, 2016; Nxumalo et al, 2020; Takele & Selassie, 2018; Takeshima, 2018). To the best of our knowledge, however, no study has investigated smallholder farmers' WTP for agricultural mechanization services in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aims to assess labor shortages related to different farm activities, estimate the WTP for mechanization services, and identify policy options for promoting smallholder mechanization services in Malawi. Previous studies in SSA and Asia showed that smallholder farmers are willing to pay for tractor‐hire services for agricultural activities such as land preparation, weeding, harvesting, threshing, and transport (Hodjo et al, 2021; Houssou et al, 2016; Nxumalo et al, 2020; Takele & Selassie, 2018; Takeshima, 2018). To the best of our knowledge, however, no study has investigated smallholder farmers' WTP for agricultural mechanization services in Malawi.…”
Section: Introductionmentioning
confidence: 99%